2008
DOI: 10.1111/j.1469-8137.2008.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

The model legume Medicago truncatula A17 is poorly matched for N2 fixation with the sequenced microsymbiont Sinorhizobium meliloti 1021

Abstract: Summary• Medicago truncatula (barrel medic) A17 is currently being sequenced as a model legume, complementing the sequenced root nodule bacterial strain Sinorhizobium meliloti 1021 (Sm1021). In this study, the effectiveness of the Sm1021-M. truncatula symbiosis at fixing N 2 was evaluated.• N 2 fixation effectiveness was examined with eight Medicago species and three accessions of M. truncatula with Sm1021 and two other Sinorhizobium strains. Plant shoot dry weights, plant nitrogen content and nodule distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 19 publications
6
102
0
2
Order By: Relevance
“…Consistent with this, we measured plant dry weight, commonly used as a proxy for measuring effectiveness of symbiosis (Terpolilli et al, 2008), and we showed that growth of mutant plants under symbiotic conditions is not adversely affected compared with wild-type plants (see Supplemental Table 1 online). In addition, histological observation of noot nodules (see Supplemental Figure 2 and Supplemental Table 2 online) showed that they have the characteristic zonation of wild-type nodules, are properly invaded by symbiotic bacteria, and contain differentiated symbiotic cells.…”
Section: The M Truncatula Noot Mutant Is a Nodule Homeotic Mutantmentioning
confidence: 73%
“…Consistent with this, we measured plant dry weight, commonly used as a proxy for measuring effectiveness of symbiosis (Terpolilli et al, 2008), and we showed that growth of mutant plants under symbiotic conditions is not adversely affected compared with wild-type plants (see Supplemental Table 1 online). In addition, histological observation of noot nodules (see Supplemental Figure 2 and Supplemental Table 2 online) showed that they have the characteristic zonation of wild-type nodules, are properly invaded by symbiotic bacteria, and contain differentiated symbiotic cells.…”
Section: The M Truncatula Noot Mutant Is a Nodule Homeotic Mutantmentioning
confidence: 73%
“…The capacity for N 2 -fixation (effectiveness) was determined by comparing yields of inoculated plants with +N controls (5 ml of 10 mM KNO 3 applied weekly). The strains were separated into three groups as described by Terpolilli et al (2008); those considered effective (E) = >75% of +N control, partially effective (PE) = >20% but <75% of +N control, ineffective (I) = <20% of +N control or no nodulation (Nod-). General analyses of variance using a 5% least significant difference (LSD) were calculated on the data sets using GenStat 12 ® (Release 12.1, Lawes Agricultural Trust, Rothamsted Experimental Station) and are shown in the figure legends where appropriate.…”
Section: Nodulation and Nitrogen Fixation Assay (Experiments 2)mentioning
confidence: 99%
“…Plates were left at room temperature for 24-36 h, before germinated seedlings were transferred into a steam-sterilised mix of river sand and yellow sand (1:1). Plants were grown using the culture system described by (Howieson et al 1995), where deficiency of N limits legume growth except where they are effectively nodulated or are supplied with nitrogen (Terpolilli et al 2008).…”
Section: Surface Sterilisation Of Seedmentioning
confidence: 99%
“…This study was undertaken to investigate the effect of co-inoculation with WSM3457 on the kinetics of nodule initiation and development in M. truncatula when the symbiosis is challenged by a low inoculum dose of rhizobia. In glasshouse experiments legumes are often inoculated with 10 7 -10 9 root nodule bacteria (Hirsch et al 2009;Howieson et al 1995;Tang et al 2001;Terpolilli et al 2008). However, when seeds are inoculated prior to sowing in the field, the inoculum density is much lower, in the order of 10 4 cells per gram of seed.…”
Section: Introductionmentioning
confidence: 99%